Pendugaan Aliran Conduit Sistem Akuifer Kawasan Karst Gua Pindul Gunung Kidul Menggunakan Metode Geolistrik Konfigurasi Wenner - Surya, Bonang Surya Utama; Reva Anindya, Silvia (UNIB Press, 2023)
Karst areas contain limestone lithology that is easily dissolved by water, so rainwater can accelerate the process of dissolving rocks below the surface and forming cavities. The hydrological system of the Pindul area has a conduit flow karst aquifer type. The components of conduit flow are open channels and pipe-like passages that have various shapes. The distribution and direction of conduit flow control the Pindul Cave karst aquifer system in Gunung Kidul. The wenner configuration resistivity geoelectric method can determine the presence of a subsurface—conduit flow in karst areas by knowing the difference in rock-specific resistance values. Resistivity geoelectric measurements were carried out using 8 tracks with each track length of 200 meters. The results of data processing and interpretation of the resistivity cross-section show the presence of conduit flow in 5 passes with a resistivity value of 0.174-25 Ωm. The results of the study can provide an overview to determine the subsurface river area.